2016
DOI: 10.1122/1.4949340
|View full text |Cite
|
Sign up to set email alerts
|

Start-up shear of concentrated colloidal hard spheres: Stresses, dynamics, and structure

Abstract: Orientation and rupture of fractal colloidal gels during start-up of steady shear flow J. Rheol. 49, 657 (2005) AbstractThe transient response of model hard sphere glasses is examined during the application of steady rate start-up shear using Brownian dynamics simulations, experimental rheology and confocal microscopy. With increasing strain, the glass initially exhibits an almost linear elastic stress increase, a stress peak at the yield point and then reaches a constant steady state. The stress overshoot ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 85 publications
10
89
0
Order By: Relevance
“…The function ϕ(γ c ) goes to saturation faster at the higher value of the parameter D. The parameter ϕ 0 is the limit value of ϕ. Namely, at the large deformations (in our case at γ c > 0.6) the long axis of the elliptic contour in the distribution g c (x, y) is oriented at the angle ϕ 0 ≈ 45 • with respect to the gradient direction (see also Refs. [11,20,32]). As it follows from Refs.…”
Section: B Critically-sized Crystalline Nuclei Under Shearmentioning
confidence: 99%
See 2 more Smart Citations
“…The function ϕ(γ c ) goes to saturation faster at the higher value of the parameter D. The parameter ϕ 0 is the limit value of ϕ. Namely, at the large deformations (in our case at γ c > 0.6) the long axis of the elliptic contour in the distribution g c (x, y) is oriented at the angle ϕ 0 ≈ 45 • with respect to the gradient direction (see also Refs. [11,20,32]). As it follows from Refs.…”
Section: B Critically-sized Crystalline Nuclei Under Shearmentioning
confidence: 99%
“…This is confirmed by results of large number of studies (Refs. [1,7,14,[23][24][25][26][27][28][29][30][31][32]). So, for example, Kumaraswamy and co-workers [22] have revealed experimentally that non-spherical ordered structures oriented along the shear direction occur for the case of polydisperse isotactic polypropylene melt under intensive shear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinhardt et al 17 studied the distortion of the pair correlation function under start-up shear. Koumakis et al 18 reported on stresses in the start-up phase of shearing, in particular on the dependence of the stress overshoot on the Peclet number and on the volume fraction, using both simulation and experiments with sterically stabilized PMMA spheres using confocal microscopy and rheological measurements. Stress overshoot in start-up and cessation of shear and the connection to the microscopic fluid structure have also been studied 19 .…”
Section: Introductionmentioning
confidence: 99%
“…During this overshoot period, the material performs a transition from solid-like to fluid-like behavior. It has been the focus of recent work to study the process of yielding in more detail [1][2][3][4][5][6][7][8]. There, we find many different definitions of yield points, each characterizing a different aspect of yielding.The simplest approach of defining a yield strain in glasses is taking the strain at the overshoot maximum γ peak .…”
mentioning
confidence: 99%